What we keep - Berg, Elizabeth (New York : Random House, 1998)
Ginny Young is on a plane, en route to see her mother, whom she hasn't seen or spoken to for thirty-five years. She thinks back to the summer of 1958, when she and her sister, Sharla, were young girls. At that time,a series of dramatic events--beginning with the arrival of a mysterious and sensual next-door neighbor--divided the family, separating the sisters from their mother. Moving back and forth in time between the girl she once was and the woman she's become, Ginny at last confronts painful choices that occur in almost any woman's life, and learns surprising truths about the people she thought she knew best.
73777
Keywords: Mothers and daughters -- Fiction; Sisters -- Fiction; Domestic fiction